The development of a disruption responsive smart room technology with attendance management system - Jennifer P. Juaneza (Northern Negros State College of Science and Technology (NONESCOST), 2023)
This paper discusses the development of a disruption responsive smart room technology with an Attendance Management System. It outlines the key features of the technology, such as the use of sensors to identify environmental changes, the creation of algorithms to comprehend and react to these changes, and the integration of smart devices to facilitate smooth communication and control. The disruptive responsive technology has transformed traditional processes and industrial practices combined with the latest smart technology that evolved locally and globally. The proponent of this study created the Development of a Disruption Responsive Smart Room Technology, which will allow modern technologies to be used to generate a substantial difference from the traditional ones. The objectives of this study were to establish an RFID (Radio Frequency Identification)-based registration and identification system for faculty and students that will help with the accuracy of attendance management and an electrical supply relay socket that will enable the function of a smart room technology that will give the faculty the power to control the devices connected to and networked with a mobile console. The automatic temperature change based on the humidity levels of the room utilizing the humidity sensor is another highlight of the study. The technology needs to be linked to a network and the internet in order to function as intended. The researcher used Developmental Research in this study and utilized the Agile Methodology, which includes all of its phases. Its purpose is to assess the research effectiveness and efficiency with an excellent rating from its respondents. The paper concludes with an evaluation of the potential issues with the technology's development and application and provides recommendations for further research in this area.